Conservation Status of Swamp Wetlands in Uasin Gishu County, Kenya - Mulei, J. M.; O. Onkware, Augostino (Africa Environmental Review Journal, 2018)
Despite their high productivity and provision of many benefits, wetland ecosystems in Kenya are still facing serious threats. In Uasin Gishu County swamp wetlands are under varying degrees of threat because of the rapid human population growth. However, inadequate investigation has been carried out on the integrity of these wetlands even though they benefit the surrounding communities. The aim of the study was to determine the conservation status of selected wetlands in the county. The objectives were to determine the main human activities in and around the swamps and to obtain the local people’s perceptions on conservation. A total of 120 informants participated in the study. The Likert Scale Scoring method, observations and informal discussions with community members were used to assess the conservation status of the swamps. The results indicated generally low conservation status of the four swamps studied. The main disturbance events included drainage and reclamation of the swamps for agricultural development, burning, and plant harvesting. Agriculture was rated as the most important use of the wetlands. There were no conservation initiatives in place. There is need to promote indigenous knowledge on conservation through education and awareness programmes with community members living around the wetlands.